Bespoke nanostars: synthetic strategies, tactics, and uses of tailored branched gold nanoparticles. Issue 14 (16th June 2021) - Siegel, Asher L.; Baker, Gary A.
Abstract : Interest in branched colloidal gold nanosystems has gained increased traction due to the structures' outstanding optical and plasmonic properties, resulting in utilization in a broad range of imaging, catalytic, and therapeutic techniques. Abstract : Interest in branched colloidal gold nanosystems has gained increased traction due to the structures' outstanding optical and plasmonic properties, resulting in utilization in techniques such as surface-enhanced spectroscopy and bioimaging, as well as plasmon photocatalysis and photothermal therapy. The unique morphologies of nanostars, multipods, urchins, and other highly branched nanomaterials exhibit selective optical and crystallographic features accessible by alterations in the respective wet-chemical syntheses, opening a vast array of useful applications. Examination of discriminatory reaction conditions, such as seeded growth ( e.g., single-crystalline vs. multiply twinned seeds), underpotential deposition of Ag(i ), galvanic replacement, and the dual use of competing reducing and capping agents, is shown to reveal conditions necessary for the genesis of assorted branched nanoscale gold frameworks. By observing diverse approaches, including template-directed, microwave-mediated, and aggregation-based methods, among others, a schema of synthetic pathways can be constructed to provide a guiding roadmap for obtaining the full range of desired branched gold nanocrystals. This review presents a comprehensive summary of such advances and these nuances of the underlying procedures, as well as offering mechanistic insights into the directed nanoscale growth. We conclude the review by discussing various applications for these fascinating nanomaterials, particularly surface-enhanced Raman spectroscopy, photothermal and photodynamic therapy, catalysis, drug delivery, and biosensing.